Pembangunan Kakas Bantu Untuk Mengukur Maintainability Index Pada Perangkat Lunak Berdasarkan Nilai Halstead Metrics dan McCabe's Cyclomatic Complexity: English - Rasio Ganang Atmaja; Bayu Priyambadha; Fajar Pradana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In the software development cycle there is a maintenance phase. In this phase, errors or defects of the software that have not been found on development or testing phase will be corrected. In this phase, software is also changing to fit the new system environment and stakeholder needs. In software development there are several reasons why it is necessary to calculate maintainability value of the software, such as the value of maintainability can help in deciding whether a software is easy to maintain or needs to be redesigned. There are several methods that can be used to measure maintainability value of the program, one is the Maintainability Index (MI). Maintainability Index is calculated based on the value of Halstead's Volume, McCabe's Cyclomatic Complexity, and line of codes. The Maintainability Index calculations system provide features for calculate Maintainability Index values of the Java source code and display graph visualizations using Java technologies. This system has been tested using unit testing, integration testing that uses Whitebox methods and validations testing that use Blackbox methods. This system has an accuracy of 98% and the time for calculating one method only takes less than 1000ms